Analisis Perilaku Bullying Siswa Sekolah Dasar Negeri 164 Pekanbaru - Septiani, Fahri; Erlisnawati, Erlisnawati; Marhadi, Hendri (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the forms of bullying behavior that occur in elementary schools, to find out the factors that cause bullying behavior in elementar and to find out efforts to deal with bullying problems in elementary schools. This type of research is qualitative with a case study approach. The data collection techniques used are observation, interviews, documentation, and triangulation. The results of this study show the forms of bullying behavior that occur in elementary schools, namely saying rude, mocking parents' names, mocking with unique calls, insulting, scorning and cheering. The factors that cause bullying behavior in elementary schools are family factors: a complete family but both parents are busy working so that they receive less attention and family factors that experience economic difficulties Mass media factor: By looking at mobile phones and television, students can be seen imitating the movie scenes they watched, as well as imitating the way they speak. Peer factor: students who do abusive words caused by free and unkind associations. The impact of bullying behavior is for the victim: not confident, being quiet, lonely, moody in class, becoming unenthusiastic to participate in learning, while for the perpetrator of bullying: Bullying perpetrators have minimal empathy in interacting with society. The efforts to handle bullying cases by providing socialization by the foundation, making strict regulations regarding bullying, setting an example, singing anti-bullying songs, teaching students to fight bullying and the existence of bullying posters in the school environment.